2010
DOI: 10.1021/cm903783w
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of Bulk Heterojunction Solar Cells Using Block Copoly(3-alkylthiophene)s

Abstract: The photovoltaic properties, charge transport, and morphology of a series of diblock conjugated copolymers, poly(3-butylthiophene)-b-poly(3-octylthiophene) (P3BT-b-P3OT), were investigated as a function of block composition. Bulk heterojunction solar cells comprising blends of P3BT-b-P3OT and [6,6]-phenyl-C71-butyric acid methyl ester (PC71BM) were found to have power conversion efficiencies as high as 3.0%, which represents factors of 1.6−9 enhancements compared to those of the homopolymers made under similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 43 publications
5
85
0
Order By: Relevance
“…79 As such devices made from poly(3-octylthiophene) (P3OT) have very low PCE of only 0.68%, in spite of chemical and band gap similarities to P3HT. 80,81 Blends and copolymers of P3HT (2b) and P3OT, as well as pure poly(3-heptylthiophene) (P3HpT), were investigated to optimize between the high charge mobility of P3HT (2b) and the extensibility of P3OT. P3HpT produced the best balance, ultimately maintaining the high crystallinity of P3HT (2b), while having a T g lower than room temperature.…”
Section: Effect Of Alkyl Side Chainsmentioning
confidence: 99%
“…79 As such devices made from poly(3-octylthiophene) (P3OT) have very low PCE of only 0.68%, in spite of chemical and band gap similarities to P3HT. 80,81 Blends and copolymers of P3HT (2b) and P3OT, as well as pure poly(3-heptylthiophene) (P3HpT), were investigated to optimize between the high charge mobility of P3HT (2b) and the extensibility of P3OT. P3HpT produced the best balance, ultimately maintaining the high crystallinity of P3HT (2b), while having a T g lower than room temperature.…”
Section: Effect Of Alkyl Side Chainsmentioning
confidence: 99%
“…In order to investigate the effect of crystallinity of P3AT -based polymers, Jenekhe et al . synthesized copolymers of butylthiophene and octylthiophene, and showed that some polymers could form lamellar crystals [15,28] . Thus, an improved hole mobility and a best PCE of 3% was achieved from b2 .…”
Section: Polythiophene Derivativesmentioning
confidence: 99%
“…A power conversion efficiency (PCE) of 0.22 % with open circuit voltage (V oc ) = 0.55 V, short due to the potential self-assembly of the block copolymers into well-defined microphase separations (Scherf et al 2008;Wang and Higashihara 2013;Yassar et al 2013). For instance, all-conjugated rod-rod block copolymers, such as poly(3-hexylthiophene)-b-poly(3-dodecylthiophene) (P3HT-b-P3DT) (Iovu et al 2005), P3HT-b-poly(3-phenoxy methylthiophene) (Ohshimizu and Ueda 2008), and poly(3-butylthiophene)-b-(poly(3-octylthiophene) (Ren et al 2010), were synthesized via the sequential monomer addition method through quasi-living KCTP. However, these all-conjugated block copolymers are all electron donors and cannot be used as single active components in BHJ solar cells due to the absence of electron acceptor.…”
Section: Introductionmentioning
confidence: 99%